Perceptions of nanotechnology utilization in food: a pilot study - Urša Kogovšek; Boris Kovač; Katarina Babnik (Journal of Engineering & Processing Management, 2017)
Nanotechnology is a science field that includes research and applications carried out in the sphere of below 100 nanometers. Nanofood is the result of the usage of nanotechnology in food production, processing, and packaging. The paper presents results of a pilot study on perceptions of nanotechnology and its use in food production. A questionnaire was developed for the purpose of the study that measured knowledge, perceptions and attitudes towards nanotechnology and nanoproducts in general and in food industry. The results of the analysis suggested lack of knowledge about nanotechnology and its utilisation in food production. Motivation of respondents to purchase nanoproducts is low, mostly due to perceptions of possible changes in food caused by the use of nanotechnology. The respondents are aware of their poor understanding of nanotechnology and perceive potential risks related to the utilisation of nanotechnology. Education of consumers in relation to nanotechnology and its utilisation in manucaturing, especially in food production, is a necessary step in future development of this field.
Keywords: Consumers; food; nanotechnology; perceptions